THE ACCOUNTANCY OF HEALTH SERVICE INSTITUTION (Research Bulletins of the Faculty of Economic Sciences, 2021)
The health service institutions are founded in order to provide medical services. They carry out not only economical purposes but also and maybe above all social purposes. It influences considerably the shape of their accountancy. It concerns above all the information that is generated be accountancy and which is necessary for management. The medical information have economical meaning which allows to make comparisons and analyses of profitability of particular services. The cost account is specific, in which a pricing of medical services is made which is immensely difficult to measure. All these reasons affect the usage of specific medical service institutions accountancy solutions.